2013
DOI: 10.1038/ki.2013.222
|View full text |Cite
|
Sign up to set email alerts
|

A community-based cross-sectional and longitudinal study uncovered asymptomatic proteinuria in Japanese adults with low body weight

Abstract: Although proteinuria is highly prevalent in obese individuals, the association between proteinuria and low body weight is equivocal. In this study we determine whether low body weight is more strongly associated with proteinuria compared with normal weight. The association between body mass index (BMI) and proteinuria was examined in a cross-sectional study of 62,582 asymptomatic individuals aged 20-70 years without known kidney diseases recruited, based on the results of medical checkups in 1999. We also exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 46 publications
4
22
0
Order By: Relevance
“…A growing body of clinical evidence has revealed that proteinuria, including albuminuria, is much more common in obese individuals than in normal-weight individuals [1820]. However, our recent study [36] and a study by Sato et al [37] showed that low-body-weight individuals may also be at increased risk of proteinuria, relative to normal-weight individuals. The currently observed association between proteinuria and habitual breakfast skipping is therefore not surprising.…”
Section: Discussionmentioning
confidence: 80%
“…A growing body of clinical evidence has revealed that proteinuria, including albuminuria, is much more common in obese individuals than in normal-weight individuals [1820]. However, our recent study [36] and a study by Sato et al [37] showed that low-body-weight individuals may also be at increased risk of proteinuria, relative to normal-weight individuals. The currently observed association between proteinuria and habitual breakfast skipping is therefore not surprising.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, Muneyuki et al . [38] indicated that the U-shape association between BMI and proteinuria were independent of traditional cardiometabolic risk factors. Since low or high BMI is related to higher proteinuria risk and mortality, we reckoned that underweight might participate in renal disease progression in IgAN patients.…”
Section: Discussionmentioning
confidence: 99%
“…32 Within our study, the prevalence of CKD in the urban definitely increased with economic levels, whereas, it was also very large in underdeveloped rural areas, possibly due to its higher proportion of malnutrition indicators, such as anaemia and underweight (15%, 12% for rural; 11%, 7% for urban). 33,34 Confronted with the characteristics above, the control of the risk factors should be strengthened to curb the potential upward shift. 35 Meanwhile, enough attention should also be paid to underdeveloped rural area, which roughly equal to a quarter of the population aged 45 years and above.…”
Section: Prevalence and Treatment Of Ckd In Chinamentioning
confidence: 99%
“…47 J-shaped relationships between BMI and risk of CKD were observed in this study, similar to the results from the longitudinal Japanese study with the outcome of proteinuria. 34 The clinical relevance and underlying mechanism of CKD in people with low body weight remains to be elucidated in future studies.…”
Section: Prevalence and Treatment Of Ckd In Chinamentioning
confidence: 99%